PENINGKATAN KETERAMPILAN SOSIAL SISWA MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW DALAM PEMBELAJARAN ILMU PENGETAHUAN SOSIAL - Arifmunandar, Radiqdiyan; Hangestiningsih, Endang; Arief, Ardian (Jurnal PGSD Musi, 2018)
Purpose of this research is to improve student's Social ability using cooperative learning type of jigsaw in studying Social class 5 gedongtengen elementary school Yogyakarta. The subject of this research is take from one class students in grade fifth which is consisten of 29 students. Data taking technique using observation, questionnare, and documentation. Average score of questionnaire in Social ability is 69%. After completition of cycle 1, average score improve and become 75%. In the second cycle questionnaire having a improvement 83%. Results of this research showing that learning process of social science having a improvement after implement of JIGSAW model of cooperative learning.